REVIEW ARTICLE IMPURITY PROFILING OF DRUGS TOWARDS SAFETY AND EFFICACY: THEORY AND PRACTICE - Kiran R. Dhangar; Rakesh B. Jagtap; Sanjay J. Surana; Atul A. Shirkhedkar (Journal of the Chilean Chemical Society, 2017)
Last decade has witnessed enormous changes in the studies of impurity profiling of drugs which can be reflected from pharmacopoeia and regulatory guidelines. The present review article is an attempt to provide comprehensive knowledge about various aspects and details about the impurity profiling in context with regulatory guidelines. Article also focused on isolation, separation and characterization techniques of impurities. It gives preliminary idea about applicability of virtual software used for studies on safety limit for impurities. The comprehensive information related to residual solvents, residual metals and genotoxicity studies of isolated impurities have also been incorporated into present article.